Depresión como factor asociado a control metabólico inadecuado en pacientes diabéticos adultos - Quiroz Cáceres, Nohely Jacoba (2019)
Chronic diseases are becoming increasingly important in health due to its high prevalence, among them we find type 2 diabetes mellitus whose complications lead to high morbidity and mortality worldwide and in our country. The World Health Organization (WHO) estimated that by 2030 the population of diabetics in the world would amount to 370 million people. In Peru, diabetes affects almost 2 million people and is the fifth-leading cause of death . That is why the risk factors that predispose and trigger diabetes have been intensively studied over time. Likewise, depression is a common neuropsychiatric disease worldwide and it is estimated that it affects more than 300 million people , it is known that it is present in a high percentage, often underestimated, within chronic diseases due to the conditions produced by These, which affect the quality of life of patients and inherently their health. It is estimated that depression is present significantly in patients with diabetes mellitus type 2 but few studies talk about depression as a risk factor for late complications of this. In the present research work was found the association between depression and late complications of type 2 diab etes mellitus, in order to seek better control over this pathology and encourage mental health research whose objective is to unite the state gap emotional - body in Health, for the welfare and improvement of patients.